Local labour concentration moderates the disemployment effects of minimum wages in China - Pedro S. Martins; Li Dai; Wenjing Duan (Global Labor Organization (GLO), 2024)
Local labour market concentration may influence firms' employment responses to minimum wages. We evaluate this hypothesis using comprehensive 1998-2007 data on China's manufacturing sector and about 1,400 hand-collected county-level minimum wages. We find that, consistently with monopsony views, the negative effects of minimum wages on employment are reduced when labour market concentration is higher. We also find positive employment effects of minimum wages, but only in some specifications and in highly concentrated labour markets (representing a relatively small share of employment). Firms' training provision is also harmed less by minimum wages in more concentrated local markets. Our findings highlight the heterogeneity of policy impacts across local labour markets.
Keywords: J31; J38; J42; 330; Minimum wages; labour market concentration; employment; monopsony; training